2004
DOI: 10.1128/jb.186.4.1191-1196.2004
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Enzymological Interaction of Bacillus subtilis Proteins Required for De Novo Pyridoxal 5′-Phosphate Biosynthesis

Abstract: Bacillus subtilis synthesizes pyridoxal 5-phosphate, the active form of vitamin B 6 , by a poorly characterized pathway involving the yaaD and yaaE genes. The pdxS (yaaD) mutant was confirmed to be a strict B 6 auxotroph, but the pdxT (yaaE) mutant turned out to be a conditional auxotroph depending on the availability of ammonium in the growth medium. The PdxS and PdxT proteins copurified during affinity chromatography and apparently form a complex that has glutaminase activity. PdxS and PdxT appear to encode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
73
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(80 citation statements)
references
References 48 publications
7
73
0
Order By: Relevance
“…PDX1 and PDX2 have been predicted to function as a glutamine amidotransferase with PDX2 as the glutaminase domain and PDX1 as the acceptor͞synthase domain. Indeed, glutaminase activity has been demonstrated for PDX2 from a number of organisms (16)(17)(18). More recently, Burns et al (19) and our own independent studies (51) have been able to reconstitute vitamin B6 formation from intermediates of glycolysis and the pentose phosphate pathway by using the PDX1 and PDX2 homologs from the Gram-positive bacterium Bacillus subtilis.…”
mentioning
confidence: 94%
“…PDX1 and PDX2 have been predicted to function as a glutamine amidotransferase with PDX2 as the glutaminase domain and PDX1 as the acceptor͞synthase domain. Indeed, glutaminase activity has been demonstrated for PDX2 from a number of organisms (16)(17)(18). More recently, Burns et al (19) and our own independent studies (51) have been able to reconstitute vitamin B6 formation from intermediates of glycolysis and the pentose phosphate pathway by using the PDX1 and PDX2 homologs from the Gram-positive bacterium Bacillus subtilis.…”
mentioning
confidence: 94%
“…Moreover, 15 N-labeling studies in yeast had indicated that the nitrogen atom of pyridoxine is derived from the amide moiety of glutamine (9,10), whereas in the E. coli pathway it is derived from glutamate (10,21). Indeed, glutaminase activity has since been demonstrated for the PDX2 proteins of B. subtilis, Saccharomyces cerevisiae, and Plasmodium falciparum (22)(23)(24), designated YaaE (PdxT), SNO1, and PDX2, respectively. However, glutaminase activity was only observed in the presence of PDX1, which was shown to co-purify with PDX2, forming a hetero-oligomeric complex as has been observed for other glutamine amidotransferases (22,23).…”
mentioning
confidence: 99%
“…Indeed, glutaminase activity has since been demonstrated for the PDX2 proteins of B. subtilis, Saccharomyces cerevisiae, and Plasmodium falciparum (22)(23)(24), designated YaaE (PdxT), SNO1, and PDX2, respectively. However, glutaminase activity was only observed in the presence of PDX1, which was shown to co-purify with PDX2, forming a hetero-oligomeric complex as has been observed for other glutamine amidotransferases (22,23). In general, glutamine amidotransferases consist of two domains, a glutaminase domain, which hydrolyzes glutamine to glutamate and ammonia, and a synthase domain that accepts and utilizes the ammonia from the glutaminase domain (19).…”
mentioning
confidence: 99%
“…Pyridoxal 5′-phosphate (PLP) is the biologically active form of vitamin B 6 and is essential for numerous enzyme reactions, including transamination, decarboxylation, racemization, and elimination in amino acid metabolism, biosynthesis of antibiotics, and DNA biosynthesis (Eliot and Kirsch, 2004;Percudani and Peracchi, 2003). As de novo PLP biosynthesis pathways exist in bacteria, fungi, protozoa, and plants, but are missing in mammals, PLP biosynthesis could be a target for developing antibiotics (Belitsky, 2004;Dong et al, 2004;Osmani et al, 1999). There are two mutually exclusive de novo pathways (deoxyxylulose 5′-phosphate (DXP)-dependent and DXP-independent) (Fitzpatrick et al, 2007;Tambasco-Studart et al, 2005).…”
Section: Introductionmentioning
confidence: 99%